Communicable Diseases Intelligence volume 3 issue 11 - 8 June 1979 - whole issue - No author listed, (Communicable Diseases Intelligence, 1979)
Whole-issue pdf, comprising: Virus reports this period Article Legionnaires' Disease in Melbourne Endocarditis due to Cardiobacterium hominis. [Brisbane, Qld.] B -lactamase producing N. gonorrhoeae. [South Australia] Intenational notes: Dengue Fever in Fiji Reye Syndrome in the U.S.A. Summary of viral identifications reported during 1978. [See amendment from CDI 79/12, page 4. "Amendment to Bulletin 79/11, Page 3, line 11. Replace "isolations" with "identifications". Similarly in line 22." [end] A case of Mycoplasma pneumoniae encephalopathy Australia - Communicable Diseases Intelligence Reporting Period - 17/05/1979 to 30/05/1979 Bulletin Number 79/11 Notifiable Diseases Reported in Australia 4th 4 Weekly Period for 1979. Bulletin 79/11 [See revised report in CDI 79/13]